Mechanism of Appointment of DPRD Chair according to National Law Perspective - Zainuddin Zainuddin (International Journal Reglement & Society (IJRS), 2021)
Democracy in the life of the state, one of which is reflected in the existence and implementation of elections. Elections are a manifestation of sovereignty held by the people. Elections held in Indonesia aim to be a means of democracy, maintain the establishment of the Unitary State of the Republic of Indonesia (NKRI), realize national goals, elect members of the legislature, elect the president and vice president. Legislative members who are elected through elections are representatives of the people in the legislature. This means that members of the legislature are representatives of the people who vote. They as representatives must have the ability or obligation to speak and act on behalf of a larger group being represented. Elections to elect representatives of the people are called legislative elections which are held to elect members of the People's Representative Council (DPR), Regional Representatives Council (DPD), and Regional People's Representative Council (DPRD). Based on Article 18 paragraph (3) of the 1945 Constitution, it is stated that provincial, district, and city regional governments have Regional People's Representative Councils whose members are elected through general elections. In a democratic country, the existence of the People's Representative Council (hereinafter abbreviated as DPR) and the Regional People's Representative Council (hereinafter abbreviated as DPRD) is a must. DPRD is a regional people's representative institution that carries out regional government functions as an equal partner to regional governments. In the structure of regional government, DPRD is located at two levels, namely at the provincial level called the Provincial DPRD and at the regency/city level it is called the Regency/Municipal DPRD. Members of the DPRD are directly elected to occupy/serve legislative positions within one period (five years). based on procedures, the purpose of this research is to find out the process of changing the leadership of the DPRD and the process of appointing the chairman of the DPRD according to the perspective of national law. In article 327 paragraphs 2 and 3 it is emphasized that in essence it is stated that the leadership of the DPRD and the chairman of the DPRD comes from the number of political parties that are counted as getting the first most seats in the Provincial DPRD, so that this also causes several pros and cons, for example taken from the example in 2015 members The East Nusa Tenggara DPRD conducted a judicial review to the Constitutional Court because they felt that their constitutional rights had been violated by the enactment of the a quo article. The Petitioner explained that the process of filling out and appointing the DPRD's equipment had eliminated his constitutional rights, then he said that as a result of this provision, the Petitioner had lost the opportunity to participate in the process of selecting the DPR's apparatus